Activity-dependent slowing of conduction velocity in uninjured L4 C fibers increases after an L5 spinal nerve injury in the rat - Shim, Beom (2006)
Growing evidence suggests that uninjured afferents may play an important role in neuropathic pain following nerve injury. The excitability of nociceptive neurons in the L4 spinal nerve appears to be enhanced following an injury to the adjacent L5 spinal nerve. In this study, we investigated whether the action-potential conduction properties of unlesioned, unmyelinated fibers are also altered. A teased-fiber technique was used to record from single C fibers from the L4 spinal nerve of the rat in vitro. Repeated electrical stimulation of the tibial nerve was used to investigate activity-dependent slowing of conduction velocity. Twin pulse stimulation at a 50 ms interpulse interval allowed investigation of supranormal conduction velocity. Blinded experiments were performed 8–10 days after sham surgery and after an L5 spinal nerve ligation (L5 SNL). Activity-dependent slowing revealed two populations of C fibers, a “nociceptor” population with a large degree of activity-dependent slowing and a “non-nociceptor” population with a smaller degree of activity-dependent slowing. Both populations showed enhanced activity-dependent slowing of conduction velocity and enhanced supranormal conduction velocities in lesioned animals compared to sham animals. Activity-dependent slowing was also enhanced after an L5 SNL in the mouse. These alterations in conduction velocity may reflect changes in expression of ion channels responsible for the membrane excitability. These data provide additional evidence that a nerve injury leads to persistent alterations in the properties of adjacent uninjured, unmyelinated fibers.